An Unusual Presentation of Primary Lymphoma of the Ilium - Mohamad Gouse; Viswanath Jayasankar; Manika Alexander (Case Reports in Medicine)
Primary bone lymphoma involving the pelvic bone is a rare entity. It does not have distinct clinical features or radiological features that are diagnostic. Biopsy is the gold standard investigation. We present a case of primary pelvic lymphoma with initial histopathological features of chronic osteomyelitis. Upon further clinical follow-up, repeat biopsy of the lesion revealed features of B-cell Non-Hodgkin’s lymphoma, thus emphasizing the need for a high index of suspicion and close clinical follow-up. This case is presented for the diagnostic dilemma and the unique feature of lymphomatous lesion mimicking chronic osteomyelitis in its early stages.